THE EFFECT OF THE ICARE MODEL ASSISTED BY CONCRETE MEDIA ON STUDENT LEARNING OUTCOMES IN INDONESIAN LANGUAGE LEARNING CLASS IV SDN 1 LAMBHEU ACEH BESAR - Ramadhani, Raihan; Safiah, Intan; Fitri, Aida (Elementary Education Research, 2024)
ICARE (introduction, connection, application, reflection and extend) is a model that makes it easy to apply the knowledge that students have learned in real life with the help of concrete media. This research aims to determine the effect of using the ICARE model assisted by concrete media on student learning outcomes in class IV Indonesian language learning at SD Negeri 1 Lambheu Aceh Besar with a problem formulation. Is there a significant influence of using the ICARE model assisted by concrete media on student learning outcomes in learning Indonesian Class IV SDN 1 Lhambeu Aceh Besar?. The approach used is a quantitative approach. The type of research is Quasi Experimental with a Posttest Only Nonequivalent Control Group design model. The research location was at SD Negeri 1 Lambheu with the population taken being all class IV students and a sample of 28 class IVA students consisting of 16 girls and 12 boys as the experimental class and class IVB as many as 31 people consisting of 19 girls and 12 men as the control class. The data collection technique is through a multiple choice test consisting of 10 questions. The analysis technique used is a data analysis technique in the form of a t-test. Based on the results of research that researchers have conducted regarding the influence of the ICARE model assisted by concrete media on student learning outcomes in learning Indonesian, exchanging or paying material for class IV SDN 1 Lhambeu Aceh Besar?. The approach used is a quantitative approach. The type of research is Quasi Experimental with a Posttest Only Nonequivalent Control Group design model. The research location was at SD Negeri 1 Lambheu with the population taken being all class IV students and a sample of 28 class IVA students consisting of 16 girls and 12 boys as the experimental class and class IVB as many as 31 people consisting of 19 girls and 12 men as the control class. The data collection technique is through a multiple choice test consisting of 10 questions. The analysis technique used is a data analysis technique in the form of a t-test. Based on the results of research conducted by researchers regarding the influence of the ICARE model assisted by concrete media on students' learning outcomes in learning Indonesian, exchange or payment materials for class IV SDN 1 Lambheu Aceh Besar, namely significant data processing results (2-tailed) of 0.000 0. .05. This means that the criteria for decision making are rejected and accepted. So the decision obtained is that there is an influence of the ICARE model assisted by concrete media on student learning outcomes in class IV Indonesian language learning at SDN 1 Lhambeu Aceh Besar.